Health and the body: The Ingram Collection at the Royal College of General Practitioners (RCGP), London, UK. (3 March to 29 May 2016). (2nd April 2016) - Kenny, Steven
Abstract: A new Ingram Collection exhibition, Health and the Body, opened for a period of two months at the Royal College of General Practitioners in London. The exhibition showcased paintings and sculptures by artists such as Eduardo Paolozzi, Barbara Hepworth, Geoffrey Clarke and Leon Underwood the artworks explored representations of the human body, and observed how these intersected with the history of general medical practice.